2014
DOI: 10.1108/ijppm-09-2013-0161
|View full text |Cite
|
Sign up to set email alerts
|

Contingency theory, performance management and organisational effectiveness in the third sector

Abstract: Purpose – The purpose of this paper is to develop a theoretical framework that explains how performance management (PM) affects the organisational effectiveness in the third sector. Design/methodology/approach – The authors adopt a two stage process in developing the theoretical framework; a systematic review of literature and theoretical developments of the framework. The underlying principles for developing the theoretical framework are mainly based on prior theoretical justification and empirical resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 83 publications
(216 reference statements)
3
60
1
10
Order By: Relevance
“…In the context of the sustainable practices, the stakeholder theory suggests that stakeholders play an important role in pressuring companies to adopt SPM practices, which in turn can lead to a competitive advantage [40,41,57]. As such, the four contingent factors that influence SPM practice are: (1) The organizational learning culture, (2) the advancement of technology, (3) globalization and (4) pressure from stakeholders, in line with the studies of [55][56][57][58]…”
Section: Development Of Hypotheses Based On the Research Modelmentioning
confidence: 82%
“…In the context of the sustainable practices, the stakeholder theory suggests that stakeholders play an important role in pressuring companies to adopt SPM practices, which in turn can lead to a competitive advantage [40,41,57]. As such, the four contingent factors that influence SPM practice are: (1) The organizational learning culture, (2) the advancement of technology, (3) globalization and (4) pressure from stakeholders, in line with the studies of [55][56][57][58]…”
Section: Development Of Hypotheses Based On the Research Modelmentioning
confidence: 82%
“…In order to facilitate the understanding of the effect of the external contingency factors in the NGOs through the environmental contingency variable, this study uses the taxonomy suggested by Wadongo and Abdel-Kader (2014), which classifies the external environment into three variables. The first is the degree of unpredictability or environmental uncertainty.…”
Section: External Contingency Factorsmentioning
confidence: 99%
“…In turn, environmental uncertainty was negatively related to data collection and performance-based rewards, while at the same time being positively related to performance indicators, strength and consistency of the performance management system and information flows of the performance management system.The second variable used in the study was the degree of intensity of environmental competition among NGOs. Normally, environmental competition is associated with private-sector companies (Wadongo & Abdel-Kader, 2014). This characteristic is normal, as private companies aim to make a profit, considering all aspects of the market, such as scarcity of resources, dispute for customers, suppliers, internal competitions, among others, which encourage the adaptation of management controls to these environmental conditions.…”
Section: External Contingency Factorsmentioning
confidence: 99%
See 2 more Smart Citations